2018
DOI: 10.1161/jaha.118.008731
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Healthcare Expenditures Among US Adults With Hypertension: National Estimates, 2003–2014

Abstract: BackgroundOne in 3 US adults has high blood pressure, or hypertension. As prior projections suggest hypertension is the costliest of all cardiovascular diseases, it is important to define the current state of healthcare expenditures related to hypertension.Methods and ResultsWe used a nationally representative database, the Medical Expenditure Panel Survey, to calculate the estimated annual healthcare expenditure for patients with hypertension and to measure trends in expenditure longitudinally over a 12‐year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
183
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(187 citation statements)
references
References 17 publications
1
183
2
1
Order By: Relevance
“…The significant increase in mortality is alarming considering the population size of the 55 and older age group is estimated to increase over the next 30 years (Fig 3C). An increasing mortality rate, with an accelerating rate of change, coupled with an increasing population size for this group may have severe economic and healthcare ramifications in the United States that far exceed current healthcare resource and expenditure estimates [25].…”
Section: Discussionmentioning
confidence: 96%
“…The significant increase in mortality is alarming considering the population size of the 55 and older age group is estimated to increase over the next 30 years (Fig 3C). An increasing mortality rate, with an accelerating rate of change, coupled with an increasing population size for this group may have severe economic and healthcare ramifications in the United States that far exceed current healthcare resource and expenditure estimates [25].…”
Section: Discussionmentioning
confidence: 96%
“…Apart from hypertension, which is a common chronic condition in the U.S. adult population (Kirkland et al, 2018), the most prevalent medical conditions in women (deployed and nondeployed) are those that share similar symptoms with Gulf War illness (also known as chronic multisymptom illness), including joint pain and stiffness, gastrointestinal upset, * Self-reported, missing data (n ¼ 330).…”
Section: Discussionmentioning
confidence: 99%
“…A study that analysed national data on the distribution of drugs in Portugal showed increased costs of medication, from €100 million to €278 million over a 6‐year period . Another study conducted in the USA reported that the annual cost of arterial hypertension medication was US$ 2371, a much higher value compared with normotensive patients, US$ 814 . High drug values may be further justified by the high prevalence of arterial hypertension, which is twice as frequent in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%